Morfopedologia e fragilidade ambiental nos fundos de vale do trecho superior do córrego Guavirá Marechal Cândido Rondon - PR - Rocha, Anderson Sandro da (2011)
The researches which aims for the mapping and analysis of morphopedological dynamics and environmental fragility of watershed are fundamental to the comprehension of the geological structure and of the processes of soil evolution and alteration in the landscape. Those studies, besides contributing to the comprehension of soil s space distribution, also make it possible to relate the macromorphologic features with the environmental characteristics of the watersheds. In that sense, the current research, developed in the periurban area of Marechal Candido Rondon city, West Parana State region, has for objective to understand and analyze the morphological condition and environmental fragility, present in the valley bottom sectors of Guavira brook watershed s superior section. This study has as objective contributing to the knowledge of organization and distribution of soils along the valley bottoms, and collaborating to the objectives of GEA group (Multidisciplinary Group of Environmental Studies), which has as finality monitoring, analyzing and contenting socioenvironmental problems of the municipality. Based on those objectives, it was privileged for the theoretical and methodological development of the research, the precepts of the pedological cover structural analysis and landscape integrated analysis, by which desk work was developed (bibliographical survey, study area delimitation, photo interpretation, elaboration of maps about soil usage, declivity, soils and environmental fragility maps); field work (geological, topographic and pedological survey) and lab work (physical and chemical soil analysis). Such procedures results permitted to comprehend the interaction of natural and atrophic elements which compose the geological structure of Guavira brook s watershed from which was possible to identify the potential and emerging fragilities of the valley bottom sectors, particularly supported by the knowledge of organization and distribution of soils, characterized by classes: a) FLUVIC CAMBISOL gleysol eutrophic; b) HAPLIC CAMBISOL typical perferric; c) RED NITOSOL typical eutroferric and d) LITHOLIC NEOSOL fragmentary eutrophic.